2017
DOI: 10.1002/acn3.414
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fumarates on inflammatory human astrocyte responses and oligodendrocyte differentiation

Abstract: ObjectiveDimethyl fumarate (DMF) is a fumaric acid ester approved for the treatment of relapsing‐remitting multiple sclerosis (RRMS). In both the brain and periphery, DMF and its metabolite monomethyl fumarate (MMF) exert anti‐inflammatory and antioxidant effects. Our aim was to compare the effects of DMF and MMF on inflammatory and antioxidant pathways within astrocytes, a critical supporting glial cell in the central nervous system (CNS). Direct effects of fumarates on neural progenitor cell (NPC) differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 42 publications
1
28
0
1
Order By: Relevance
“…This effect might ameliorate astrocytic damage in active lesions, including the retraction of perivascular astrocyte end feet along basal lamina ( 16 ), to reduce leakage across the BBB and the cortical surface ( 163 ). DMF also inhibits secretion of pro-inflammatory cytokines and chemokines by astrocytes and microglial cells, independent of changes in antioxidant gene expression ( 164 ). Therefore, in addition to its effect on the peripheral immune system, DMF has a direct impact on the CNS that involves protective and anti-inflammatory effects on astrocytes.…”
Section: Direct Modulation Of Reactive Astrocyte Activity By Ms Treatmentioning
confidence: 99%
“…This effect might ameliorate astrocytic damage in active lesions, including the retraction of perivascular astrocyte end feet along basal lamina ( 16 ), to reduce leakage across the BBB and the cortical surface ( 163 ). DMF also inhibits secretion of pro-inflammatory cytokines and chemokines by astrocytes and microglial cells, independent of changes in antioxidant gene expression ( 164 ). Therefore, in addition to its effect on the peripheral immune system, DMF has a direct impact on the CNS that involves protective and anti-inflammatory effects on astrocytes.…”
Section: Direct Modulation Of Reactive Astrocyte Activity By Ms Treatmentioning
confidence: 99%
“…The molecular masses of the proteins are indicated on the left-hand side. entiation of oligodendrocyte precursor cells (OPC) to oligodendrocytes, as evidenced by increased expression of O4 (47). Recently, Zuchero et al described that early oligodendrocyte differentiation from OPCs is accompanied by the extension of processes containing ordered arrays of actin filaments, requiring polymerized actin and low cofilin activity (48).…”
Section: Novel Targets Of Dimethyl Fumarate Action In Neuronal Cellsmentioning
confidence: 99%
“…On the other hand, data obtained from murine and human astrocytes treated with DMF, and activated with IL-1β, show no significant difference in HO-1 and NQO-1 expression at the mRNA level. Some authors have suggested that the effect of DMF may be cell specific or even Nrf2 independent [10]. Animal studies by Linker et al [23], showing Nrf2 activation in the chronic phase of EAE induced in mice treated with DMF, revealed increased Nrf2 expression in neurons, oligodendrocytes, and astrocytes, but not in microglia or in T cells, in the spinal cords collected from the animals on the 74 th DPI.…”
Section: Discussionmentioning
confidence: 99%